Dampak Ekonomi Pengembangan Wisata Pulau Bokori Terhadap Masyarakat Lokal Bajo Di Kabupaten Konawe - Darwan, Darwan; Yunus, Lukman; Fyka, Samsul Alam; Limi, Muhammad Aswar (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
The purpose of this study was to determine the economic impact of developing bokori island tourism on local Bajo communities. This research was conducted at the center of the tourist site of Bokori Island, namely in Mekar Village, Soropia District, Konawe Regency. The sample is determined by several categories, namely 58 local people using the slovin method, 5 business units determined by purposive sampling and the workforce determined by the census. This study is survey research that uses quantitative and qualitative descriptive analysis. Analysis of the data used is Marine Ecotourism for Atlantic Area (META) (2001), which is measured using two types of multipliers, namely Keynesian local income multiplier effect, and income multiplier ratio, namely the value that shows how much the direct impact of visitor spending has an impact on the local economy. The research result is the value of economic impact obtained from the Keynesian Income Multiplier value of 0.1, the value of the Type I Ratio Income Multiplier is 1.6, and the value of the Type II Ratio Income Multiplier is 2.0 The value of the multiplier effect is one (= 1 ) shows that the existence of a tourist attraction in Bokori Island has an economic impact and affects the economy of the local community. Although the Keynesian Income Multiplier value shows that the economic impact of Pualu Bokori tourism development is still low.